Clock Gene Nr1d1 Alleviates Retinal Inflammation Through Repression of Hmga2 in Microglia - Wang Z; Huang Y; Chu F; Ji S; Liao K; Cui Z; Chen J; Tang S (Dove Medical Press, 2021)
Zhijie Wang,1,2 Yinhua Huang,1,2 Feixue Chu,3 Shangli Ji,2 Kai Liao,1,2 Zekai Cui,2 Jiansu Chen,1,2,4,5 Shibo Tang1,2,6 1Aier School of Ophthalmology, Central South University, Changsha, People's Republic of China; 2Aier Eye Institute, Aier Eye Hospital Group, Changsha, People's Republic of China; 3Department of Ophthalmology, Hangzhou Xihu Zhijiang Eye Hospital, Hangzhou, People's Republic of China; 4Key Laboratory for Regenerative Medicine, Jinan University, Guangzhou, People's Republic of China; 5Institute of Ophthalmology, Jinan University, Guangzhou, People's Republic of China; 6CAS Center for Excellence in Brain Science and Intelligence Technology, Chinese Academy of Sciences, Shanghai, People's Republic of ChinaCorrespondence: Shibo Tang; Jiansu Chen Email tangshibo@vip.163.com; chenjiansu2000@163.comPurpose: Retinal inflammation is involved in the pathogenesis of several retinal diseases. As one of the core clock genes, Nr1d1 has been reported to suppress inflammation in many diseases. We investigated whether pharmacological activation of Nr1d1 can inhibit retinal inflammation and delineated the mechanisms of Nr1d1 in alleviating microglia activation.Methods: Lipopolysaccharide (LPS) induced mice models were used to examine the effects of SR9009 (agonist of NR1D1) treatment on inflammatory phenotypes in vivo. Anti-inflammatory effects of Nr1d1 and associated mechanisms were investigated in the BV2 microglia cell line, and in primary retinal microglia in vitro.Results: SR9009 treatment alleviated LPS-induced inflammatory cell infiltration, elevated cytokine levels and morphological changes of the microglia in mice models. In LPS-stimulated BV2 cells and primary retinal microglia, SR9009 suppressed cytokine expressions by inhibiting the NF-κB signaling pathway. Moreover, SR9009 treatment increased the levels of the M2 phenotype marker (CD206) and the proportions of ramified microglia. Suppression of Nr1d1 with siRNA reversed the inhibitory effects of SR9009 on cytokine production in BV2 cells. RNA-seq analysis showed that genes that were upregulated following Nr1d1 knockdown were enriched in inflammatory-associated biological processes. Subsequently, ChIP-seq of NR1D1 in BV2 was performed, and the results were integrated with RNA-seq results using the Binding and Expression Target Analysis (BETA) tool. Luciferase assays, electrophoretic mobility shift assay (EMSA), qPCR and Western blotting assays revealed that NR1D1 binds the promoter of Hmga2 to suppress its transcription. Notably, overexpressed Hmga2 in activated microglia could partly abolish the anti-inflammatory effects of Nr1d1.Conclusion: The clock gene Nr1d1 protects against retinal inflammation and microglia activation in part by suppressing Hmga2 transcription.Keywords: clock genes, Rev-erbα, Nr1d1, retinal inflammation, Hmga2